2013
DOI: 10.1111/1471-0528.12510
|View full text |Cite
|
Sign up to set email alerts
|

Availability and access in modern obstetric care: a retrospective population‐based study

Abstract: Objective To assess the availability of obstetric institutions, the risk of unplanned delivery outside an institution and maternal morbidity in a national setting in which the number of institutions declined from 95 to 51 during 30 years.Design Retrospective population-based, three cohorts and two cross-sectional analyses. Methods Geographic Information Systems software for travel zone calculations. Cross-table and multiple logistic regression analysis of change over time and regional differences. World Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…Thirteen were preterm breech presentations (nine between 22 and 25 gestational weeks and four between 26 and 37 weeks). Figure 1 shows a bimodal distribution of gestational age, with modes at 24 and 38 weeks and a median of 28 weeks (range [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Figure 2 shows the bimodal birthweight distribution, with modes at 750 and 3400 g, and the median at 905 g (range 510-4146 g).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen were preterm breech presentations (nine between 22 and 25 gestational weeks and four between 26 and 37 weeks). Figure 1 shows a bimodal distribution of gestational age, with modes at 24 and 38 weeks and a median of 28 weeks (range [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Figure 2 shows the bimodal birthweight distribution, with modes at 750 and 3400 g, and the median at 905 g (range 510-4146 g).…”
Section: Resultsmentioning
confidence: 99%
“…Despite data showing higher incidence of unplanned OOI births in Norway than in other European countries, there is no evidence of a decline (1,(36)(37)(38)(39)(40)(41)(42). The national guidelines for antenatal care have no information on when and how to seek care when labor starts (43), and the Norwegian healthcare system appears to lack the ability to learn and share safety lessons about unplanned OOI births.…”
Section: Discussionmentioning
confidence: 99%
“…The annual rate of unplanned births in Norway has increased from approximately 4/1000 births in 1979–1983 to 7/1000 births during the last 10 years . A study for the period 1967–1988 found a similar PMR for births during transport to hospital and other births during the last 3 years studied .…”
Section: Introductionmentioning
confidence: 94%
“…There has been a trend in many countries towards centralization of births to fewer and larger units. In Norway, the number of birth institutions went down from 158 in the year 1972 to 82 in 1990 and 57 in the year 2000 (>10 deliveries/year), and has now levelled off at 51 . The perinatal mortality rate (PMR) decreased simultaneously, from 21.9/1000 births for the years 1967–1971 to 4.9/1000 in 2011 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation